2011
DOI: 10.1111/j.1440-1681.2011.05498.x
|View full text |Cite
|
Sign up to set email alerts
|

Tanshinone IIA suppresses lung injury and apoptosis, and modulates protein kinase B and extracellular signal‐regulated protein kinase pathways in rats challenged with seawater exposure

Abstract: 1. Tanshinone IIA (TIIA) is one of the main active components of the Chinese herb, Danshen. In the present study, we investigated the role of apoptosis in seawater exposure-induced acute lung injury (ALI), and explored the effects of TIIA on lung injury, apoptosis, and protein kinase B (Akt) and extracellular signal-regulated protein kinase (ERK) pathways in seawater-challenged rats. The rats were randomly divided into four groups: (i) naive group, no drug was given; (ii) TIIA control group, TIIA (50 mg/kg) wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
24
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 38 publications
4
24
0
Order By: Relevance
“…We here first demonstrated that Tan ⅡA could reduce BLMeinduced CD-68-positive macrophage infiltration in rat lung tissue. Our study along with several previous studies [17,32] reveals an anti-inflammatory role of Tan ⅡA in lung diseases. However, whether Tan ⅡA had antifibrotic potential in lung fibrosis remains poorly understood.…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…We here first demonstrated that Tan ⅡA could reduce BLMeinduced CD-68-positive macrophage infiltration in rat lung tissue. Our study along with several previous studies [17,32] reveals an anti-inflammatory role of Tan ⅡA in lung diseases. However, whether Tan ⅡA had antifibrotic potential in lung fibrosis remains poorly understood.…”
Section: Discussionsupporting
confidence: 52%
“…Antitumor activities, cardioprotective, and neuroprotective effects of Tan ⅡA have been reported in many earlier studies [13e15]. Notably, Tan ⅡA has also been proven to effectively mitigate seawater exposure-induced lung injuries such as lung edema and vascular leakage in rodents [16,17], suggesting that Tan ⅡA has a protective activity in pulmonary diseases. Fu et al [18] have found that Tan ⅡA blocks EMT in MCF-7 and HCC1973 breast cancer cell lines Q5 .…”
Section: Introductionmentioning
confidence: 89%
“…We also showed that pretreatment with TIIA greatly decreased the production of pro-inflammatory cytokines in both LPS-treated mice and cultured macrophages, which most likely correlated with the inhibition of HIF-1α expression by TIIA [9] . Moreover, we further indicated that pretreatment with TIIA could significantly attenuate the severity of ALI in seawater-challenged rats through the depression of macrophage migration inhibitory factor [12] , aquaporins (AQP) 1 and AQP5 expression [11] and apoptosis [13] and up-regulation of Na + ,K + -ATPase activity [10] .…”
Section: Discussionmentioning
confidence: 97%
“…Apoptotic cells were found in the damaged alveolar epithelium of patients with ARDS [37] , and in murine models of pulmonary fibrosis and LPS [34,35,38] and seawater exposure-induced ALI [13] . Although TIIA could prevent and treat lung injury induced by LPS, little is known about the effect of TIIA on apoptosis in mice with ALI.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation